ПРАВОВОЕ РЕГУЛИРОВАНИЕ АТОМНОЙ ПРОМЫШЛЕННОСТИ РЕСПУБЛИКИ КАЗАХСТАН - Satbayeva, A.M. (Journal of actual problems of jurisprudence, 2019)
This article reveals the actual state of the law governing the nuclear industry. In the research provides a detailed analysis of existing normative and legal acts in the field of legal regulation of the nuclear industry.